Development of fuzzy-pid cascade control system for differential-drive wheeled mobile robot - Mohd Saifizi Saidon (School of Mechatronic Engineering, 2012)
This study focuses on the control systems implementations of an intelligent autonomous mobile robot called Mobile Autonomous Robot (MAR).